Baju Bodo from a Cultural Perspective: Exploring the Meaning of Traditional Dress in Bugis-Makassar Culture - Abu Haif; Risdayanti Risdayanti; Muhammad Awal Rafi Abdillah Rajab; Muhammad Raehan Ramdhani; Hikmawati Z; Ahmad Syihab (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to examine the symbolic meanings of Baju Bodo, the traditional attire of the Bugis-Makassar community, analyze its aesthetic interpretations in contemporary contexts, and explore the transformation of its meanings amid social and cultural change. Employing a qualitative approach with a descriptive-interpretative method, this study is based on a library research design. Data were collected through an extensive review of relevant scholarly literature, previous studies, and cultural documents, and were analyzed using Roland Barthes’ semiotic framework and the perspective of cultural aesthetics. The findings reveal that Baju Bodo functions not merely as traditional clothing but also as a cultural symbol that represents social stratification, moral values, collective identity, and the worldview of the Bugis-Makassar community. The symbolism embedded in its colors, forms, and patterns of use reflects a complex system of cultural values and social norms that has been transmitted across generations. Furthermore, the study demonstrates that modernization, globalization, social media, and the fashion industry have contributed to a transformation in the meaning of Baju Bodo, shifting its function from a predominantly symbolic cultural artifact toward a stronger emphasis on aesthetic expression and individual representation. Nevertheless, Baju Bodo continues to serve as a significant marker of cultural identity and local heritage. Therefore, its preservation should extend beyond maintaining its physical form to encompass the safeguarding and revitalization of the symbolic meanings and cultural values embedded within it.